Prodigy: Legend Series #2 - Lu, Marie, 1984- (New York, NY : G. P. Putnam's Sons, 2012)
June and Day make their way to Las Vegas where they join the rebel Patriot group and become involved in an assassination plot against the Elector in hopes of saving the Republic.
Keywords: Fugitives from justice -- Fiction; Criminals -- Fiction; Soldiers -- Fiction; War -- Fiction; Government, Resistance to -- Fiction; Assassination -- Fiction; Science fiction